Whole-Genome Sequences of Eight Clinical Isolates of Burkholderia pseudomallei from Melioidosis Patients in Eastern Sri Lanka - Jayasinghearachchi, Himali S. (Microbiol Resour Announc, 2019)
Here, we report whole-genome sequences (WGS) of eight clinical isolates of Burkholderia pseudomallei obtained from melioidosis patients with sepsis in eastern Sri Lanka.